The Role of Emotional Marketing in Achieving Marketing Ambidexterity: An Analytical Study of Opinions from a Sample of Commercial Bank Managers in Duhok Governorate - Shukri, Abdulwahid Taha; Hamid, Nizar Ahme (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2025)
This study investigates the role of emotional marketing in achieving marketing ambidexterity within commercial banks in Duhok Governorate, Kurdistan Region of Iraq. Emotional marketing, operationalized through aesthetic, utilitarian, and conscious emotions, is analyzed in relation to marketing ambidexterity dimensions, namely opportunity exploration, opportunity exploitation, and marketing agility. Drawing on organizational ambidexterity theory and consumer psychology, the study addresses a critical gap in understanding how emotional marketing strategies enhance both efficiency and adaptability in the banking sector of emerging markets. The research adopts a descriptive-analytical design, combining theoretical review and empirical investigation. Data were collected from 75 managers across commercial banks using a structured questionnaire, supported by interviews and observations. Factor analysis and simple linear regression, conducted with SPSS V.26, were employed to validate constructs and test hypotheses. The results demonstrate that all three dimensions of emotional marketing significantly influence marketing ambidexterity, with aesthetic emotions contributing most strongly to opportunity exploration, utilitarian emotions to exploitation, and conscious emotions to marketing agility. Collectively, emotional marketing explained 53.49% of the variance in marketing ambidexterity outcomes. These findings highlight the strategic value of emotional engagement in fostering both stability and innovation in banking practices. The study contributes to marketing and organizational theory by extending ambidexterity research into the domain of emotional marketing in emerging economies. Practically, it provides insights for bank managers on integrating emotional strategies to enhance customer loyalty, service innovation, and sustainable competitiveness.